Politik Global dan Wacana Etika Religius: Antara Tabatabai dan Hamka - Purkon Hidayat (Jurnal ICMES, 2018)
The dynamics of global politics are increasingly complex. Various approaches commonly used to analyze these dynamics often fail to capture the essence of it so that new approaches are needed that take into account various dimensions, including ethics, which are starting to become a concern of related experts. Through Frost's approach to the important position of the normative paradigm in the study of International Relations, this article offers a discourse on religious ethics as the initial pioneering alternative thinking of political philosophy. In this article, the ethical theory of contemporary Iranian philosopher, Allamah Tabatabai, is explored with consideration that Middle Eastern geopolitics influenced the birth of this thought. The Tabatabai thought is elaborated with the idea of religious ethics from the great Southeast Asian thinker, Buya Hamka. The technical consideration for choosing these two figures is because there is a close interdisciplinary approach, namely interpretations, Sufism and philosophy. The study found a close link between the thought of Tabatabai and Hamka in religious ethics with global political issues. By carrying out further research, it is possible to elaborate this finding for developing the basis of the metatheory of Political Science and International Relations in Islamic perspective.